Kisarasa Youtube Channel's Gastronomic Storytelling: A Narrative Paradigm Study - Wahyudi, Sulistiyo Joko; Rahmanto, Andre Noevi; Naini, Albert Muhammad Isrun (PT FORMOSA CENDEKIA GLOBAL, 2024)
Consumer preferences for food and drinks have now changed. Consumers are now emphasizing emotional needs and the stories behind culinary products. Consumers are interested in the origin of raw materials, manufacturing techniques, and the values instilled by producers, thereby creating an emotional connection with the food they consume. Social media such as Instagram, TikTok, and YouTube are crucial in introducing new culinary trends and unique dining experiences. In particular, food vloggers on YouTube use the platform to share their gastronomic storytelling. This qualitative research uses a content analysis approach with narrative paradigm theory to analyze how the structure and accuracy of gastronomic storytelling on YouTube provide information about culinary products while enriching viewers' emotional and intellectual understanding of gastronomy